Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5dt00863h
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-based complexes for water oxidation

Abstract: Activation of organometallic Ir precatalysts can yield either homogeneous or heterogeneous water-oxidation catalysts with very high activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 100 publications
2
118
0
Order By: Relevance
“…Recently, they showed that when molecular iridium dimer catalyst 3 was anchored to an ITO surface, a very low onset potential was found of only 14 mV as reported by the authors (Figure , 3@MO x ) . This dimeric complex presumably operates through the ROC mechanism . The dimeric nature of this type of iridium catalysts is also supported by kinetic analysis of the reaction progress .…”
Section: Experimental Examplesmentioning
confidence: 52%
See 1 more Smart Citation
“…Recently, they showed that when molecular iridium dimer catalyst 3 was anchored to an ITO surface, a very low onset potential was found of only 14 mV as reported by the authors (Figure , 3@MO x ) . This dimeric complex presumably operates through the ROC mechanism . The dimeric nature of this type of iridium catalysts is also supported by kinetic analysis of the reaction progress .…”
Section: Experimental Examplesmentioning
confidence: 52%
“…Therefore, the WNA mechanism dominates, resulting in a higher overpotential. Another class of molecular catalysts with a very low overpotential are the iridium catalysts reported by Brudvig, Crabtree and co‐workers . Recently, they showed that when molecular iridium dimer catalyst 3 was anchored to an ITO surface, a very low onset potential was found of only 14 mV as reported by the authors (Figure , 3@MO x ) .…”
Section: Experimental Examplesmentioning
confidence: 74%
“…Successively, many other molecular Ir WOCs were reported, and many excellent and exhaustive reviews recently appeared in the literature , , . Herein, the focus is on the stability and activity of Ir WOCs, two strictly interlocked and crucial aspects.…”
Section: Molecular Ir Wocsmentioning
confidence: 99%
“…The OER is important for many renewable energy conversion technologies, such as photoelectrochemical cells, regenerative fuel cells, and electrolyzers [1,4,5]. In acid systems, Ir and Ru-based oxides are common catalysts for the OER, while in alkaline environments non-precious transition metal oxides based on Ni, Fe, and Co are commonly employed [6][7][8][9][10]. In all cases, OER catalysts suffer from considerable overpotential losses, limiting the efficiency of hydrogen generation by water electrolysis processes [11].…”
Section: Introductionmentioning
confidence: 99%